Cultural Encounters in Modern Productions of Greek Tragedy - Wilmer, S.E. (Nordic Theatre Studies, 2016)
The exiled character in need of asylum is a recurrent theme in ancient Greek tragedy. In many of these plays, we see uprooted and homeless persons seeking sanctuary, and for the ancient Greeks, hospitality was an important issue. Many of these plays have been updated to comment on the current social and political conditions of refugees and often reflect on the notion of hospitality, something which both Emmanuel Levinas and Jacques Derrida considered to be fundamental to ethics. Recently there has been a series of demonstrations and occupations of public spaces by asylum seekers that has gained considerable news coverage. In Austria a group of about sixty refugees (from the Afghanistan-Pakistan border area) occupied the famous Votiv church in the middle of Vienna in 2012 and went on hunger strike. In Germany a large group of asylum seekers marched from various parts of the country to Berlin where they occupied the square at the Brandenburg Gate before being allowed to establish a tent community in Kreuzberg. In Hamburg a group of 80 asylum seekers who came to Germany via Lampedusa found refuge in St Pauli church, and it was there that Nicholas Stemann presented a first reading of Elfriede Jelinkek’s play Die Schutzbefohlenen in September 2013. More recently right-wing groups have mounted weekly marches through Dresden to call for a halt to immigration, and these have been contested by simultaneous counter-demonstrations in favour of immigrants and refugees. In this paper I will consider several adaptations of Greek tragedy that highlight cultural encounters between the local population and those arriving from abroad who are looking for asylum. In particular I will examine Stemann’s production that has been running at the Thalia Theater in Hamburg since September 2014, and features asylum seekers from Lampedusa on stage who beg the audience for the right to remain in Germany.